2016
DOI: 10.4236/ojml.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between EFL Teachers’ Job Satisfaction, Self-Efficacy, and Their Spiritual Sense of Well-Being

Abstract: The purpose of this study was to examine the relationship among Iranian EFL teachers' job satisfaction, self-efficacy, and their spiritual well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Conversely, the perception of internal job satisfaction was perceived higher than the external one (Akkaya & Akyol, ). No relationship was found between job satisfaction and self‐efficacy, and no significant relationship was observed between a sense of efficacy and the spiritual well‐being of the teachers (Rastegar & Moradi, ). All factors of participative decision‐making were found to be significantly influenced by and positively related to the sense of efficacy and job satisfaction of the Vietnamese secondary teachers (Dat, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, the perception of internal job satisfaction was perceived higher than the external one (Akkaya & Akyol, ). No relationship was found between job satisfaction and self‐efficacy, and no significant relationship was observed between a sense of efficacy and the spiritual well‐being of the teachers (Rastegar & Moradi, ). All factors of participative decision‐making were found to be significantly influenced by and positively related to the sense of efficacy and job satisfaction of the Vietnamese secondary teachers (Dat, ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant negative relationship was shown between job satisfaction and the spiritual well‐being of teachers. No significant relationship was found between a sense of efficacy and teachers’ spiritual well‐being (Rastegar & Moradi, ). Interpersonal relations as an environmental variable correlated significantly with subjective well‐being and the character strength of teachers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, there are a few studies in the literature that suggest that there is a relationship between teacher wellbeing and job satisfaction [39]- [41]. For instance, Rastegar and Moradi [41] suggested that teachers' job satisfaction and spiritual wellbeing were significantly and negatively correlated. Besides, Kidger et al [40] stated that the poor wellbeing of teachers was strongly associated with job dissatisfaction.…”
Section: Resultsmentioning
confidence: 99%